Opini Siswa terhadap Siswa yang Mengalami Kecanduan Game Online di Kelas XI IPS 1 SMAN 2 Tanggul - Soeharno, Ageng; Pamungkas, Abad Adi (Jurnal Parenting dan Anak, 2023)
The emergence of deviant behavior among teenagers is caused by their inability to control their emotions. The tendency of teenagers to engage in deviant behavior can be controlled if they have well-developed emotional intelligence. Good emotional intelligence can help teenagers manage their emotions appropriately, enabling them to adapt to their environment. Family is one of the factors that influence emotional intelligence because the relationship between parents and teenagers has an impact on the emotional intelligence of teenagers. The aim of this study is to determine the difference in emotional intelligence between students whose parents are divorced and those whose parents are not (intact) at SMA PGRI Purwoharjo. This study is a comparative quantitative research involving 38 students with divorced parents and 38 students with intact parents at SMA PGRI Purwoharjo, selected using quota sampling technique. The study utilized an emotional intelligence scale (30 items, α = 0.866) adapted from Wardani's research (2019). The results of this study indicate that there is no difference in emotional intelligence between students with divorced parents and those with intact parents at SMA PGRI Purwoharjo (r = 0.759, p > 0.05).